ICT Project Management System(IPMS) - Kyatuhire Shilah (Uganda Christian University, 2024)
This report is all about an internship exercise carried out at National ICT Innovation Hub that lasted for the period of 10 weeks as summarized below. Chapter one talks about introduction about the agency, background, general set up, ownership and management, objectives of the organization, organization structure, activities the organization does and the clients of the agency. Chapter two also talks about introduction, specific objectives and activities undertaken during the field attachment. It further talks about the relationships between the field activities and the theories learnt in lecture rooms. Chapter three introduces us to lessons learnt, skills attained by the intern, experience gained, how the field work impacted on the intern’s professional development. Chapter four exposes the challenges that we encountered during the field training by the internee, challenges National ICT Innovation Hub and their respective resolutions. Chapter five talks about recommendations and conclusions, however it should be noted that the recommendations are not only to the agency but also to the university at large.
FINAL YEAR PROJECT REPORT